Kyai's Role As an Educator and Moral Builder In Islamic Education In Pesantren: A Response to the Controversy of Trans7 Broadcast - Afifah, Farida Nur (Fahmina: Jurnal Pendidikan Islam, 2025)
This research examines the role of kyai as a central actor in Islamic education in Islamic boarding schools, especially as educators, moral coaches, and guardians of the moral authority of the ummah in the midst of the challenges of mass media representation. Pesantren as a traditional Islamic educational institution has an important role in the formation of the character, spirituality, and moral values of students. However, in the context of contemporary media, pesantren and kyai figures are often represented simplifying and tend to be negative, thus potentially weakening public trust in the moral authority of pesantren schools. This research explicitly uses the library research method with a qualitative-descriptive approach. Data was obtained through the analysis of scientific literature, official documents, and public statements related to the issue of pesantren representation in the media. The limitation of this study lies in the non-use of direct empirical data from kyai, pesantren communities, and media practitioners, so that the findings produced are conceptual and normative. The scope of the study was limited to the controversy of Trans7 which drew public criticism because it was considered to degrade the values and traditions of the Islamic boarding school. This case is used as an illustrative study to understand the relationship between the mainstream media and Islamic boarding schools. The analysis was carried out using the theoretical framework of moral authority kyai, Islamic moral education, and media representation theory. The results of the study show that kyai plays the role of uswah hasanah, spiritual guide, and director of integral moral education. Disproportionate media representation has the potential to undermine the symbolic legitimacy and moral authority of the kyai.